Effect of Enteromorpha Polysaccharide on Intestinal Bacteria and Short Chain Fatty Acids in Obese Golden Hamsters - Shiying HUANG; Jiedong CHEN; Mengyuan HAN; Caihong XU; Fuchuan GUO (Shipin gongye ke-ji, 2023)
Objective: To investigate the effect of Enteromorpha polysaccharide (EP) on blood lipids and intestinal bacteria in obese golden hamsters. Method: Forty male golden hamsters were randomly divided into four groups, including control group (ND), model group (HFD), low-dose EP group (LEP, 300 mg/kg·BW), and high-dose EP group (HEP, 450 mg/kg·BW). The ND group was fed an ordinary diet, while the other three groups were given a high-fat diet. Among the high-fat diet groups, the LEP and HEP groups were continuously administered EP aqueous solution intragastrically. Twelve weeks later, the serum lipid levels were evaluated, the diversity and structural changes in the gut bacteria were examined using 16S rDNA sequencing, and the short-chain fatty acid concentration in faeces was examined using a gas chromatography flame ionisation detector (GC-FID). Results: After 12 weeks, the body weight, serum total cholesterol (TC), triglyceride (TG), and low-density lipoprotein cholesterol (LDL-C) of hamsters in the HFD group were considerably higher than those in the ND group (P<0.05). In contrast, high-dose EP treatment led to a significant decrease in serum TC, TG, LDL-C, and alanine aminotransferase (ALT) levels (P<0.05). Results of 16S rDNA sequencing revealed that at the phylum level the proportion of Firmicutes/Bacteroidetes was substantially higher in the HFD group than in the ND group (P<0.05). However, the level of Firmicutes/Bacteroidetes was much lower in the HEP group, compared to the HFD group (P<0.05). At the genus level, Eubacterium_coprostanoligenes_group and Lachnospiraceae UCG-006 were more abundant in the HFD group than in the ND group (P<0.05). Following high-dose EP intervention, the relative abundance of Eubacterium_coprostanoligenes_group and Lachnospiraceae_UCG-006 fell significantly, compared to the HFD group (P<0.05). Additionally, a high-fat diet feeding resulted in a decrease in the content of short-chain fatty acids in faeces, while high-dose EP intervention significantly increased the short-chain fatty acid content in faeces (P<0.05). Conclusion: The administration of EP alleviates the metabolic disorders of obese golden hamsters fed with a high-fat diet by moderating the composition of intestinal bacteria and enhancing the production of short-chain fatty acids.